Analisis Manajemen Resiko Menggunakan Metode COSO ERM Dalam Kegiatan Bongkar Muat Barang (Studi Kasus: Kegiatan Bongkar Muat Barang di PT. Pelabuhan Tanjung Priok Cabang Panjang) - Slamet Pamujianto; Faqih Muzakki; Himawan Aditya Pratama; Umar Abdul Aziz; Handoyo Widiyanto (Jurnal Baruna Horizon, 2025)
Abstract. This study aims to analyze the implementation of risk management based on the Committee of Sponsoring Organizations Enterprise Risk Management (COSO ERM) in loading and unloading activities at PT. Pelabuhan Tanjung Priok, Panjang Branch. The method used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results indicate that the application of COSO ERM assists in the identification and management of operational risks. During cement unloading, risks include accidents and being struck by cement bags. During oil palm kernel meal loading, risks identified include truck overturning due to overloading, damage to hatch ladders, and the potential for workers to be struck by oil palm kernel meal nets. The study's conclusions confirm that COSO ERM can be an effective framework for managing loading and unloading risks, although improvements are needed in supervision, work facilities, and the presentation of safety procedures.